SOL ( SAVE OUR LANGUAGE ) PERMAINAN EDUKATIF DALAM MEMPERKENALKAN BAHASA BALI BAGI ANAK–ANAK PAUD DHARMA PRAJA DENPASAR - I Gusti Agung Satya Pratiwi; Ni Made Prahatyaningrat Maha yoga; Maudilla Anwar Putri; I Wayan Andi (Jurnal Bakti Saraswati (JBS): Media Publikasi Penelitian dan Penerapan Ipteks, 2018)
Sumarjan & Partana (2002:20) that the language is often thought of as a product of social or cultural products, in fact, are part and parcel of that culture. The language can be considered a mirror of his time. This means that the language was in a period of particular hosts what's going on in the community, depending on the culture of the area in question. The Balinese language as a regional language, where the language of Bali is the characteristic of the nation in Bali which differentiates it from other areas. It is very important to instill an interest of the child to know and learn about the Balinese language, besides Indonesia language as the national language and is also English Language as the international language. At an early age is the right age to introduce children to a variety of languages. Because at that age the children very like to imitate people around him, both from the deed. Then let the age we teach it – a good thing and later beneficial for yourself, your family and the environment. PAUD Dharma Praja Denpasar its located in the town center and the settlement where the use of language in place of Bali is currently rarely used as the language of communication daily